PENGARUH BUDAYA ORGANISASI TERHADAP HUBUNGAN ANTARA SISTEM INFORMASI AKUNTANSI MANAJEMEN DAN KINERJA MANAJERIAL (Studi pada Perguruan Tinggi Swasta di Kota Banda Aceh) - Syamsidar, Syamsidar (Jurnal Mentari, 2012)
This research is conducted at Private Universities in Banda Aceh and aimed at knowing the influence of the management accounting information system on the managerial performance as well as knowing that the organization culture strengthens the relationaship between the  management accounting information system  and the managerial performance at Private Universities in Banda Aceh. The respondents in this research include authorities at faculty and university levels at Private Universities in Banda Aceh. This research users 54 samples from a population of 116 people who are chosen through cluster random sampling. The data used are primary data which are collected through questionnaires distributed directly to the respondents. The technique of the data analysis used is multiple linear regression. The result of this research shows that the management accounting information system  has negative influence on the managerial performance at Private Universities in Banda Aceh. The organization culture strengthens the relationship between the accounting information system and the  managerial performance. Keywords: Management accounting information system, organization culture and managerial performance     DAFTAR PUSTAKA   Chenhall, R.H dan Morris, (1986), The Impact of Structure, Environment and Interpdence on The Perceived Usefulness of Management Accounting System. The Accounting Review Vol 61. No. 1 Evelyne dan Juniarti, 2002, Hubungan karakteristik informasi yang dihasilkan oleh sistem informasi akuntansi manajemen terhadap kinerja manajerial pada perusahaan-perusahaan manufaktur di Jawa Timur, Jurnal Akuntansi dan Keuangan, Vol. 5 No. 2 Nopember 2003 Faisal, 2006, Analisis Pengaruh Intensitas Persaingan dan Variabel Kontekstual terhadap Penggunaan Informasi Sistem Akuntansi Manajemen dan Kinerja Unit Bisnis dengan Pendekatan Partial least Square, Simposium Nasional Akuntansi IX Garrison, Noroen, Brewer, 2006, Manajerial Accounting, Edisi 11 Buku 1, Jakarta, Salemba empat Laksamana, Arsono, Muslichah, 2002, Pengaruh Teknologi informasi, saling ketergantungan, Karakteristik Sistem Akntansi Manajemen terhadap Kinerja Manajerial, Jurnal Akuntansi dan Keuangan Vol 4 No. 2 Nopember : http;//puslit.petra.ac.id/journals/accountins/ Mahoney, Thomas, T.H, Jerdee, dan S.J. Carroll, (1963), Development of Managerial Performance A Research Approach, South Western Publishing. Maryasih Lilis dan Fazli Syam BZ, 2006, Sistem Akuntansi Manajemen, Perspesi ketidakpastian lingkungan, desentralisasi dan kinerja organisasi (studi empiris pada perusahaan manufaktur di Provinsi NAD, Simposium Nasional Akuntansi ke-9 Padang Mia, L., Rodert H. Chenhall (1994), The Usefulness of Management Accounting System, Functional Different And Managerial Effectiveness, Accounting, Organization and Society, Vol 19 No. 1 Mulyadi, 2001, Akuntansi Manajemen, konsep manfaat dan rekayasa, edisi ketiga, Jakarta : salemba empat.